Ethnic conflict and international politics : explaining diffusion and escalation - Lobell, Steven E., 1964-; Mauceri, Philip (New York : Palgrave Macmillan, 2004)
Combining theoretical analyses with case studies, this book increases understanding of the internationalization, diffusion and escalation of ethnic conflict. The essays stand at the nexus of comparative politics and international relations, examining the influence on ethnic conflict of the weakening of state institutional structures, the role of non-state regional and international actors, changes in the ethnic balance of power, and the degree of economic, social, and cultural integration within the regional or global system. The variety of approaches provides useful analytical tools for students, while the diversity of cases from different regions gives the reader a sense of the scope of such problems.
Diffusion and escalation of ethnic conflict / Steven E. Lobell, Philip Mauceri -- Third-party states in ethnic conflict : identifying the domestic determinants of intervention / David Carment, Patrick James -- Modeling the internationalization of ethnic conflict : an application to Northern Ireland and South Africa / Neal G. Jesse, Marc V. Simon -- Identities unbound : escalating ethnic conflict in post-Soviet Azerbaijan, Georgia, Moldova, and Tajikistan / Shale Horowitz -- Internationalization of ethnic conflict in the Balkans : the breakup of Yugoslavia / Kristen P. Williams -- Internationalization as an explanation : the development of ethnic conflict in Latin America / Philip Mauceri -- Diffusion and escalation in the great lakes region : the Rwandan genocide, the rebellion in Zaire, and Mobutu's overthrow / John James Quinn -- The regionalization, internationalization, and the perpetuation of conflict in the Middle East / Jeffrey W. Helsing -- The impact of international diffusion on the escalation of the Sri Lankan conflict / Robert C. Oberst.
Includes bibliographical references (pages 181-197) and index.
Keywords: Since 1989; Ethnic conflict; World politics -- 1989-; International relations; Conflict management; Kongress -- Cedar Falls (Iowa) -- 2001.; Cross-cultural studies